Problems of Political Education of Indigenous Communities in Guaranteeing the Political Rights of Orang Rimba in Jambi Province - Darmadi, Darmadi; Tauvani, A Yuli; Aziz, Arfan; Rafii, Muhammad (The Islamic Education and Multiculturalism Foundation, 2024)
Political education for a number of indigenous peoples in Indonesia is one of the important measures in carrying out the democratic party. The political rights of the Orang Rimba have received less attention by election organizers, political parties and the government, one of which is marked by the absence of an identity card as a prerequisite for being able to exercise their voting rights. This research aims to explore the guarantee of the political rights of the Orang Rimba through political education. The method used is qualitative research and enriched by library studies by utilizing relevant literature sources to deepen the political education that has been received by the Orang Rimba. The results obtained show that political education has been carried out by the local government, and election organizing agencies, and the Indonesian Conservation Community WARSI. Limited knowledge in political education for Orang Rimba is an obstacle to political education to the fullest. Facing the General Election, Regional Head Election, and Legislative Election, the Provincial KPU has facilitated and educated the election for the Orang Rimba. This is a recognition of the political rights of the Orang Rimba, namely participation in the democratic process and providing access to political information for indigenous peoples.